Immunomodulatory Activity of Robusta Green Coffee Extract on Macrophage Phagocytosis and Lymphocyte Proliferation in Vitro - Habibi, Habibi; Lestari, Rahayu Dwi; Muchtaromah, Bayyinatul (Program Study of Biology, Science and Technology Faculty, UIN Maulana Malik Ibrahim Malang, 2023)
Robusta green coffee contains a large quantity and variety of polyphenols and flavonoids which are known to have antioxidant and anti-inflammatory properties. This research to investigate the immunomodulatory activity of Robusta green coffee extract on macrophage activity stimulated with lipopolysaccharide (LPS) and lymphocyte proliferation. Macrophages were isolated from mice peritoneal tissue, and Lymphocytes were isolated from lymph organs. The immunomodulatory activity on macrophages was evaluated based on Active Phagocytes Cells (APC) and the proliferation of lymphocytes was evaluated by the MTT Assay which was previously given extracts with varying concentrations (20 µg/ml, 40 µg/ml, 50 µg/ml, 60 µg/ml, 70 µg/ml), then the data were analyzed by ANOVA (α=0.05). The aqueous extracts of Robusta green coffee significantly affects macrophage activity and lymphocyte proliferation in vitro. The extract was decrease the percentage of phagocytosis (PP) macrophage stimulated with LPS, however there was increase phagocytosis capacity (PC) and lymphocyte proliferation stimulation index is 3, illustrating the extract has a low immunomodulatory effect on lymphocyte proliferation. Based on these results, Robusta green coffee extract holds potential as an immunomodulatory agent, affecting against macrophage phagocytosis and lymphocyte proliferation.